Examining the Factors Influencing Online Purchase Intention: A Digital Marketing Perspective (International Journal of Scientific Research in Science and Technology, 2025)
This study explores the key determinants influencing online purchase intention in the digital marketplace. The findings indicate that various digital marketing strategies and consumer perceptions play a crucial role in shaping purchase decisions. Notably, while trust and engagement drive positive purchase behaviour, perceived risk also holds significance, suggesting that consumers acknowledge potential risks but proceed with purchases due to mitigating factors such as brand credibility, return policies, and digital security measures. The study provides valuable insights for businesses aiming to optimize their online presence, enhance customer trust, and improve digital marketing effectiveness. By leveraging data-driven strategies, businesses can refine consumer interactions and boost purchase confidence. The research contributes to the growing body of knowledge on online consumer behaviour, offering practical implications for marketers, policymakers, and e-commerce platforms in designing more effective engagement and conversion strategies.
Keywords: Consumer Behaviour; E-commerce; Digital Marketing; Purchase Intention; Online Shopping Behaviour